Prehospital management of earthquake crush injuries: A collective review - Fikri M. Abu-Zidan; Kamal Idris; Arif Alper Cevik (Turkish Journal of Emergency Medicine)
Earthquakes are natural disasters which can destroy the rural and urban infrastructure causing a high toll of injuries and death without advanced notice. We aim to review the prehospital medical management of earthquake crush injuries in the field. PubMed was searched using general terms including rhabdomyolysis, crush injury, and earthquake in English language without time restriction. Selected articles were critically evaluated by three experts in disaster medicine, emergency medicine, and critical care. The medical response to earthquakes includes: (1) search and rescue; (2) triage and initial stabilization; (3) definitive care; and (4) evacuation. Long-term, continuous pressure on muscles causes crush injury. Ischemia–reperfusion injury following the relieving of muscle compression may cause metabolic changes and rhabdomyolysis depending on the time of extrication. Sodium and water enter the cell causing cell swelling and hypovolemia, while potassium and myoglobin are released into the circulation. This may cause sudden cardiac arrest, acute extremity compartment syndrome, and acute kidney injury. Recognizing these conditions and treating them timely and properly in the field will save many patients. Majority of emergency physicians who have worked in the field of the recent Kahramanmaraş 2023, Turkey, earthquakes, have acknowledged their lack of knowledge and experience in managing earthquake crush injuries. We hope that this collective review will cover the essential knowledge needed for properly managing seriously crushed injured patients in the earthquake field.